2022
DOI: 10.3390/wevj13080144
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Reduction by Echelon Utilization of Retired Vehicle Power Batteries in Energy Storage Power Stations

Abstract: With the enhancement of environmental awareness, China has put forward new carbon peak and carbon neutrality targets. Electric vehicles can effectively reduce carbon emissions in the use stage, and some retired power batteries can also be used in echelon, so as to replace the production and use of new batteries. How to calculate the reduction of carbon emission by the echelon utilization of retired power batteries in energy storage power stations is a problem worthy of attention. This research proposes a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is reported that when echelon utilization of spent battery reaches 40%, the total environmental impact is reduced by 25–40% according to a life cycle assessment (Figure c,d) . Yu et al calculated the carbon emission in energy storage power stations by using a BYD power battery. It indicated that 242.652 kg of carbon emission reduction can be achieved when a 1 kWh echelon utilization LFP battery is applied.…”
Section: Echelon Utilizationmentioning
confidence: 99%
“…It is reported that when echelon utilization of spent battery reaches 40%, the total environmental impact is reduced by 25–40% according to a life cycle assessment (Figure c,d) . Yu et al calculated the carbon emission in energy storage power stations by using a BYD power battery. It indicated that 242.652 kg of carbon emission reduction can be achieved when a 1 kWh echelon utilization LFP battery is applied.…”
Section: Echelon Utilizationmentioning
confidence: 99%
“…The growing adoption of electric vehicles (EVs) has marked a significant shift in the mobility paradigm, bringing promises of sustainability and emission reduction [1][2][3][4]. These battery-powered vehicles represent a crucial alternative to internal combustion engine vehicles, aligning with global efforts to address climate change.…”
Section: Introductionmentioning
confidence: 99%